2008
DOI: 10.1038/nature07213
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory networks define phenotypic classes of human stem cell lines

Abstract: Stem cells are defined as self-renewing cell populations that can differentiate into multiple distinct cell types. However, hundreds of different human cell lines from embryonic, fetal, and adult sources have been called stem cells, even though they range from pluripotent cells, typified by embryonic stem cells, which are capable of virtually unlimited proliferation and differentiation, to adult stem cell lines, which can generate a far more limited repertory of differentiated cell types. The rapid increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
336
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 326 publications
(352 citation statements)
references
References 38 publications
10
336
1
Order By: Relevance
“…ESC markers include the surface marker antigens (Tra series, SSEA series, GCT series, HLA, and CD markers), OCT4 and other genomic markers for the three primordial germ layers, confirmation of pluripotency by the production of teratomas in immunodeficient mice, stability of normal karyotype with serial culture, alkaline phosphatase positiveness, telomerase production, the ability to differentiate into tissues originating from all three primordial germ layers, confirmation of function, and a full transcriptome profiling to confirm the expression of ''stemness'' characteristics [Bongso et al, 2005]. Through such an analysis it is evident that genomic similarities and differences surface between stem cell lines, sources, and types [International Stem Cell Initiative, 2007;Muller et al, 2008]. Unlike ESCs, MSCs have less specific markers that define them.…”
Section: What Is the True Definition Of A Bona Fide Stem Cell?mentioning
confidence: 99%
“…ESC markers include the surface marker antigens (Tra series, SSEA series, GCT series, HLA, and CD markers), OCT4 and other genomic markers for the three primordial germ layers, confirmation of pluripotency by the production of teratomas in immunodeficient mice, stability of normal karyotype with serial culture, alkaline phosphatase positiveness, telomerase production, the ability to differentiate into tissues originating from all three primordial germ layers, confirmation of function, and a full transcriptome profiling to confirm the expression of ''stemness'' characteristics [Bongso et al, 2005]. Through such an analysis it is evident that genomic similarities and differences surface between stem cell lines, sources, and types [International Stem Cell Initiative, 2007;Muller et al, 2008]. Unlike ESCs, MSCs have less specific markers that define them.…”
Section: What Is the True Definition Of A Bona Fide Stem Cell?mentioning
confidence: 99%
“…S3). To explore these signatures further, we used a recently derived protein-protein interaction subnetwork characterizing pluripotency and stemness (the 'PluriNet') 35 and found it was preferentially upregulated only in TβSC-A (Fig. 3d).…”
Section: Tgf Regulates Normal Human Breast Epithelial Subpopulationsmentioning
confidence: 99%
“…We unexpectedly found that CoREST binds to a significantly greater number of genomic sites (1,820) compared to REST and encompassing a larger proportion of unique target genes in NSCs. 71 These included many loci encoding factors that are part of pluripotency networks 83 and individual and composite Oct4/Sox2/Nanog transcriptional networks; 84 those with critical roles in NSC maintenance, lineage restriction and neurogenesis; those involved in epigenetic regulatory networks, including genes targeted by brain-related miRNAs (e.g., miR-124a, miR-9 and miR-132); and those linked to specific disease states associated with deregulation of NSC functions (i.e., cancer stem cells), including glioblastoma multiforme. By contrast, we found that both REST and CoREST target genes included factors implicated in Huntington's disease, a disorder linked to deregulation of REST subcellular localization and function.…”
mentioning
confidence: 99%